Crucial genes associated with diabetic nephropathy explored by microarray analysis. Issue 1 (December 2016) - Wang, Zhikui; Wang, Zhaoxia; Zhou, Zhongqi; Ren, Yueqin
Abstract Background This study sought to investigate crucial genes correlated with diabetic nephropathy (DN), and their potential functions, which might contribute to a better understanding of DN pathogenesis. Methods The microarray dataset GSE1009 was downloaded from Gene Expression Omnibus, including 3 diabetic glomeruli samples and 3 healthy glomeruli samples. The differentially expressed genes (DEGs) were identified by LIMMA package. Their potential functions were then analyzed by the GO and KEGG pathway enrichment analyses using the DAVID database. Furthermore, miRNAs and transcription factors (TFs) regulating DEGs were predicted by the GeneCoDis tool, and miRNA-DEG-TF regulatory network was visualized by Cytoscape. Additionally, the expression of DEGs was validated using another microarray dataset GSE30528. Results Totally, 14 up-regulated DEGs and 430 down-regulated ones were identified. Some DEGs (e.g.MTSS1, CALD1 andACTN4 ) were markedly relative to cytoskeleton organization. Besides, some other ones were correlated with arrhythmogenic right ventricular cardiomyopathy (e.g.ACTN4, CTNNA1 andITGB5 ), as well as complement and coagulation cascades (e.g.C1R andC1S ). Furthermore, a series of miRNAs and TFs modulating DEGs were identified. The transcription factor LEF1 regulated the majority of DEGs, such asITGB5, CALD1 andC1S . Hsa-miR-33a modulated 28 genes, such asC1S . Additionally, 143 DEGs (one upregulated gene and 142 downregulated genes) were also differentially expressed in another dataset GSE30528. Conclusions The genes involved in cytoskeleton organization, cardiomyopathy, as well as complement and coagulation cascades may be closely implicated in the progression of DN, via the regulation of miRNAs and TFs.